2013
DOI: 10.1152/ajprenal.00303.2013
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase regulates the vacuolar H+-ATPase via direct phosphorylation of the A subunit (ATP6V1A) in the kidney

Abstract: (28 -30, 49). We have demonstrated that in kidney intercalated cells and in epididymal clear cells, which share a common developmental origin in the Wolffian duct, the V-ATPase redistributes from the apical membrane to the cytosol with stimulation of the metabolic sensor AMPK (16,18). In our previous studies we first identified the V-ATPase A subunit as an AMPK substrate using the unbiased "MudSeeK" proteomic screening method and subsequently showed that the V-ATPase A subunit is phosphorylated directly by AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…The diffuse intracellular localization induced by the AMPK activator AICAR was also associated with a qualitative decrease in V-ATPase-associated fluorescence in the S3 segment tubule cells, a finding that we had observed previously in collecting duct intercalated cells of rat kidney slices treated with AICAR (22). We then tested whether acute AMPK activation for 75 min affected the steady-state levels of the V-ATPase A subunit, a subunit that is directly phosphorylated by AMPK (1,23). Quantification of the anti-V-ATPase A subunit immunoblot signal (Fig.…”
Section: Pka Agonists Induce Apical Membrane Accumulation Of the V-atsupporting
confidence: 51%
See 2 more Smart Citations
“…The diffuse intracellular localization induced by the AMPK activator AICAR was also associated with a qualitative decrease in V-ATPase-associated fluorescence in the S3 segment tubule cells, a finding that we had observed previously in collecting duct intercalated cells of rat kidney slices treated with AICAR (22). We then tested whether acute AMPK activation for 75 min affected the steady-state levels of the V-ATPase A subunit, a subunit that is directly phosphorylated by AMPK (1,23). Quantification of the anti-V-ATPase A subunit immunoblot signal (Fig.…”
Section: Pka Agonists Induce Apical Membrane Accumulation Of the V-atsupporting
confidence: 51%
“…In addition, the V 0 sector "a" subunit (ATP6V0A) senses endosomal acidification by recruiting ARNO in the proximal tubule (30). Our group also showed that the metabolic sensor AMP-activated protein kinase (AMPK) inhibits V-ATPase apical accumulation in kidney intercalated cells and in epididymal clear cells (22,23) via phosphorylation at Ser-384 in the V-ATPase A subunit (1).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…We did not observe such differences in the response of the apical transporters pendrin and H ϩ -ATPase. It seems unlikely to anticipate identification of a single or unique acid sensor in the kidney because current evidence suggests a complex network of kinases [e.g., Pyk2 adhesion kinase (34,39,58), ErbB1/2 tyrosine kinase (87), and AMPK (2)], enzymes [e.g., ammoniagenic enzymes (24,25,43) and soluble adenylyl cyclase (14,64)], G protein-coupled receptors like GPR4 (23,88) or OGR1 (63) or CaSR (28,73), the insulin receptor-related receptor (InsR-RR) (68), ion channels [e.g., TASK2 (101)], and transporters [e.g., vATPase (2,62)], which may all be involved in the response to a reduction in pH. Furthermore, multiple sensors may offer advantages based on different ranges of pH sensitivity, or cellular and subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led to an intense search for the pHsensing mechanism within the intercalated cells. For example, the H 1 -ATPase in type A intercalated cells is acutely activated (within minutes to hours) by kinases such as protein kinase A (PKA), while it is acutely inhibited by the metabolic sensor AMP activated protein kinase (AMPK) ( Figure 5) (72)(73)(74). This downregulation of the proton pump by AMPK is preliminary evidence that intercalated cell function can be altered when the tubule is under metabolic stress, such as under conditions of ischemia.…”
Section: Acid-base Sensing In Intercalated Cellsmentioning
confidence: 99%